CONSTRUCTION OF JOURNALISTIC COMMUNICATION ONLINE XPOSFILE MEDIA - Kun Wazis; Ahmad Hayyan Najikh (Program Studi Komunikasi dan Penyiaran Islam Pascasarjana UIN KHAS Jember, 2023)
This research article reveals the problems faced by the Ashri Jember Islamic boarding school media, namely Xposfile. The main problem is that the Xposfile editorial team has not fully implemented the Press Law, Cyber Media Guidelines and Journalistic Code of Ethics in reporting on the online media Xposfile.com Based on descriptive research, it was found that intensive Islamic boarding school journalistic assistance can improve news and opinion products on the online media Xposfile. First, constructive improvements in the narrative side of news and opinion texts. Second, improving online media management which can gradually prepare credible journalists.